Transboundary water management : principles and practice - Earle, Anton; Jägerskog, Anders; Öjendal, Joakim (Earthscan, 2010)
The management of water resources across boundaries, whether sub-national or international, is one of the most difficult challenges facing water managers today. The upstream exploitation or diversion of groundwater or rivers can have devastating consequences for those living downstream, and transboundary rivers can provide a source of conflict between nations or states, particularly where water resources are scarce. Similarly, water based-pollution can spread across borders and create disputes and a need for sound governance. This book is the first to bring together in a concise and accessible.